2014
DOI: 10.1002/eat.22336
|View full text |Cite
|
Sign up to set email alerts
|

Ask and you shall receive: Desire and receipt of feedback via Facebook predicts disordered eating concerns

Abstract: Results of the current study provide preliminary evidence that seeking and receiving negative feedback via social networking sites can increase risk for disordered eating attitudes, and suggest that reducing maladaptive social networking usage may be an important target for prevention and intervention efforts aimed at reducing disordered eating attitudes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
0
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 18 publications
2
86
0
12
Order By: Relevance
“…Findings revealed that receiving negative comments in response to status updates concerning personal life was associated with higher levels of weight, shape, and eating concerns at the end of the 31 day period (Hummel and Smith 2015). In addition, individuals who tended to seek feedback on Facebook but received negative feedback reported higher levels of dietary restraint (Hummel and Smith 2015). Similarly, among a sample of female college students, maladaptive Facebook usage, defined as using Facebook for social comparison or negative self-evaluation purposes, predicted increases in bulimic symptoms and episodes of over-eating 4 weeks later (Smith et al 2013).…”
Section: Correlational and Longitudinal Studiesmentioning
confidence: 98%
See 2 more Smart Citations
“…Findings revealed that receiving negative comments in response to status updates concerning personal life was associated with higher levels of weight, shape, and eating concerns at the end of the 31 day period (Hummel and Smith 2015). In addition, individuals who tended to seek feedback on Facebook but received negative feedback reported higher levels of dietary restraint (Hummel and Smith 2015). Similarly, among a sample of female college students, maladaptive Facebook usage, defined as using Facebook for social comparison or negative self-evaluation purposes, predicted increases in bulimic symptoms and episodes of over-eating 4 weeks later (Smith et al 2013).…”
Section: Correlational and Longitudinal Studiesmentioning
confidence: 98%
“…In an innovative study, researchers coded participants' status updates posted on Facebook during a 31-day period, as well as other users' responses to these updates. Findings revealed that receiving negative comments in response to status updates concerning personal life was associated with higher levels of weight, shape, and eating concerns at the end of the 31 day period (Hummel and Smith 2015). In addition, individuals who tended to seek feedback on Facebook but received negative feedback reported higher levels of dietary restraint (Hummel and Smith 2015).…”
Section: Correlational and Longitudinal Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The interactive nature of social networking provides boundless opportunities for appearance comparisons and appearance‐related interactions with peers (Fardouly, Diedrichs, Vartanian, & Halliwell, ). Indeed, the interactive nature of social media appears to contribute to increases in disordered eating (Hummel & Smith, ).…”
Section: Introductionmentioning
confidence: 99%
“…All of the studies described in the preceding paragraph utilized nonclinical samples, and only one assessed for clinically significant eating disorder symptoms (with 13.6% of the sample reporting scores in the clinically significant range) . However, it is possible that Facebook could also have negative consequences for patients with clinical eating disorders, particularly for individuals who have received treatment in a group setting.…”
Section: Introductionmentioning
confidence: 99%